The Sulfolipids 2′-O-Acyl-Sulfoquinovosyldiacylglycerol and Sulfoquinovosyldiacylglycerol Are Absent from a Chlamydomonas reinhardtii Mutant Deleted in SQD1 - Riekhof, Wayne R. (The American Society for Plant Biologists, 2003)
The biosynthesis of thylakoid lipids in eukaryotic photosynthetic organisms often involves enzymes in the endoplasmic reticulum (ER) and the chloroplast envelopes. Two pathways of thylakoid lipid biosynthesis, the ER and the plastid pathways, are present in parallel in many species, including Arabidopsis, but in other plants, e.g. grasses, only the ER pathway is active. The unicellular alga Chlamydomonas reinhardtii diverges from plants like Arabidopsis in a different way because its membranes do not contain phosphatidylcholine, and most thylakoid lipids are derived from the plastid pathway. Here, we describe an acylated derivative of sulfolipid, 2′-O-acyl-sulfoquinovosyldiacylglycerol (ASQD), which is present in C. reinhardtii. Although the fatty acids of sulfoquinovosyldiacylglycerol (SQDG) were mostly saturated, ASQD molecular species carried predominantly unsaturated fatty acids. Moreover, directly attached to the head group of ASQD was preferentially an 18-carbon fatty acid with four double bonds. High-throughput robotic screening led to the isolation of a plasmid disruption mutant of C. reinhardtii, designated Δsqd1, which lacks ASQD as well as SQDG. In this mutant, the SQD1 ortholog was completely deleted and replaced by plasmid sequences. It is proposed that ASQD arises from the sugar nucleotide pathway of sulfolipid biosynthesis by acylation of the 2′-hydroxyl of the sulfoquinovosyl head group. At the physiological level, the mutant showed increased sensitivity to a diuron herbicide and reduced growth under phosphate limitation, suggesting a role for SQDG and/or ASQD in photosynthesis as conducted by C. reinhardtii, particularly under phosphate-limited conditions.